ANALISIS KOMPETENSI SOSIAL GURU DALAM PEMBELAJARAN GEOGRAFI PADA MASA PANDEMI COVID-19 - Nurfitka, Dini; Asriati, Nuraini; Harjanti, Diah Trismi (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
This research aims to determine the social competence of teachers in learning geography at SMA Negeri 1 Sungai Raya during the COVID-19 pandemic. The type of research used in this research is descriptive using qualitative methods. The data sources for this study were the geography teachers, the principal, and three students in grades X, XI, XII IPS at SMA Negeri 1 Sungai Raya. This study's data collection techniques were through observation, interviews, and documentation. The data collection tools used were observation guidelines, interview guidelines, and documentation tools. The analysis in this study was presented in a qualitative descriptive manner using two key informants and four supporting informants. The results showed that 1) Teachers in the geography learning process used written communication methods more often during the COVID-19 pandemic. 2) Teachers' communication and information technology  were  laptops, smartphones, WhatsApp, and google classroom applications in the learning process. There are no obstacles for teachers in using the technology devices, only limited quotas for students and teachers. 3) The way teachers interact and socialize in the learning process is considered suitable for the students.